Răspuns :
[tex]x = - 0.1(6) + \frac{7}{8} + ( - 0.08(3))[/tex]
[tex]x = - \frac{16 - 1}{90} + \frac{7}{8} - \frac{83 - 8}{900} [/tex]
[tex]x = - \frac{15}{90} + \frac{7}{8} - \frac{75}{900} [/tex]
[tex]x = - \frac{1}{6} + \frac{7}{8} - \frac{1}{12} [/tex]
[tex]x = - \frac{4}{24} + \frac{21}{24} - \frac{2}{24} [/tex]
[tex]x = \frac{ - 4 + 24 - 2}{24} [/tex]
[tex]x = \frac{18}{24} [/tex]
[tex]x = \frac{3}{4} [/tex]
[tex]y = - 3.1(6) + ( + 3 \frac{7}{8} ) + ( - 1.08(3))[/tex]
[tex]y = - 3 \frac{16 - 1}{90} + \frac{31}{8} - 1 \frac{83 - 8}{900} [/tex]
[tex]y = - 3 \frac{15}{90} + \frac{31}{8} - 1 \frac{75}{900} [/tex]
[tex]y = - 3 \frac{1}{6} + \frac{31}{8} - 1 \frac{1}{12} [/tex]
[tex]y = - \frac{19}{6} + \frac{31}{8} - \frac{13}{12} [/tex]
[tex]y = - \frac{76}{24} + \frac{93}{24} - \frac{26}{24} [/tex]
[tex]y = \frac{ - 76 + 93 - 26}{24} [/tex]
[tex]y = - \frac{9}{24} [/tex]
[tex]y = - \frac{3}{8} [/tex]
[tex]x + y = \frac{3}{4} + ( - \frac{3}{8} )[/tex]
[tex]x + y = \frac{3}{4} - \frac{3}{8} [/tex]
[tex]x + y = \frac{6 - 3}{8} [/tex]
[tex]x + y = \frac{3}{8} [/tex]